2019
DOI: 10.1038/s41436-019-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variants in USP7 cause a neurodevelopmental disorder with speech delays, altered behavior, and neurologic anomalies

Abstract: PurposeHaploinsufficiency of USP7, located at chromosome 16p13.2, has recently been reported in seven individuals with neurodevelopmental phenotypes, including developmental delay/intellectual disability (DD/ID), autism spectrum disorder (ASD), seizures, and hypogonadism. Further, USP7 was identified to critically incorporate into the MAGEL2-USP7-TRIM27 (MUST), such that pathogenic variants in USP7 lead to altered endosomal F-actin polymerization and dysregulated protein recycling.MethodsWe report 16 newly ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 26 publications
(46 reference statements)
1
68
0
1
Order By: Relevance
“…This includes its significant role in genome stability, where USP7 regulates the well-characterized p53/Mdm2 signaling axis ( Li et al, 2004 ), along with many other factors that will be addressed in detail in this review. USP7 is an essential enzyme; its homozygous knockout in mice results is early embryonic lethality ( Kon et al, 2010 ) and no human individuals have been identified who are USP7 homozygous-null ( Fountain et al, 2019 ). Heterozygous loss-of-function USP7 mutations have, however, been identified in 23 individuals, all of whom have experienced neurodevelopmental disorders – characterized by developmental delay/intellectual disability (DD/ID), speech delay, behavioral anomalies and autism spectrum disorder – as well as physical characteristics that include dysmorphic facial features ( Hao et al, 2015 ; Fountain et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes its significant role in genome stability, where USP7 regulates the well-characterized p53/Mdm2 signaling axis ( Li et al, 2004 ), along with many other factors that will be addressed in detail in this review. USP7 is an essential enzyme; its homozygous knockout in mice results is early embryonic lethality ( Kon et al, 2010 ) and no human individuals have been identified who are USP7 homozygous-null ( Fountain et al, 2019 ). Heterozygous loss-of-function USP7 mutations have, however, been identified in 23 individuals, all of whom have experienced neurodevelopmental disorders – characterized by developmental delay/intellectual disability (DD/ID), speech delay, behavioral anomalies and autism spectrum disorder – as well as physical characteristics that include dysmorphic facial features ( Hao et al, 2015 ; Fountain et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…USP7 is an essential enzyme; its homozygous knockout in mice results is early embryonic lethality ( Kon et al, 2010 ) and no human individuals have been identified who are USP7 homozygous-null ( Fountain et al, 2019 ). Heterozygous loss-of-function USP7 mutations have, however, been identified in 23 individuals, all of whom have experienced neurodevelopmental disorders – characterized by developmental delay/intellectual disability (DD/ID), speech delay, behavioral anomalies and autism spectrum disorder – as well as physical characteristics that include dysmorphic facial features ( Hao et al, 2015 ; Fountain et al, 2019 ). While diseases caused by pathogenic somatic mutations of USP7 are rare, the aberrant expression of USP7 is much more frequent, resulting in deregulation of numerous pathways and contributing to disease states that include non-small cell lung cancer ( Masuya et al, 2006 ) and prostate cancer ( Song et al, 2008a ).…”
Section: Introductionmentioning
confidence: 99%
“…Partial ankyloglossia and median grooved tongue could be congenital defects linked to breast feeding difficulties of those patients. [22][23][24] All studied PWS patients had infantile hypotonia and at least two PWS facial features during neonatal and early childhood period, while sixteen patients (94.1%) had feeding difficulties. At the time of examination all studied patients presented with hypotonia.…”
Section: Resultsmentioning
confidence: 99%
“…Usp7 localizes in both cytoplasm and nucleus and counteracts respectively SCF Slimb and Hib-Cul3-mediated Ci degradation ( Figure 5A) [106]. In mouse Usp7 knockout is lethal [103,104], while in human its mutations and deletions have been recently identified in children suffering from neurodevelopmental disorders [105]. ligases Similarly, USP7 binds all GLI factors in mammals, and these interactions are favored by HH and hindered by SUFU [106].…”
Section: Usp7mentioning
confidence: 99%
“…In mouse Usp7 knockout is lethal [103,104], while in human its mutations and deletions have been recently identified in children suffering from neurodevelopmental disorders [105]. ligases function to maintain the HH pathway activity [106].…”
Section: Usp7mentioning
confidence: 99%